Assessing impact velocity and temperature effects on crashworthiness properties of cork material. (August 2017) - Ptak, M.; Kaczynski, P.; Fernandes, F.A.O.; de Sousa, R.J. Alves
Highlights: Assessment of crashworthiness properties for impact energies from 120 J to 850 J allows expanding the application of the material to a wider range of safety applications. Three different type of agglomerate cork evaluated with 3 distinct grain sizes. Assessment of temperature influence on agglomerated cork crashworthiness properties. Abstract: Impact tests used to certify safety devices are becoming more severe with higher impact energies. Currently, there is a need of liner materials to withstand significant amounts of impact energy without complete deterioration. In addition, these liner materials should have the capacity to keep low accelerations to protect their user. Due to this increasing tendency of having higher impact energies, by using the same liner materials, liners are becoming thicker. Thus, there is also a need for new liner materials that can maintain an adequate thickness in order to permit sophisticated designs. This paper assesses the capacity of three different types of agglomerated cork to withstand large quantities of impact energy. Impact tests with a 9 kg impact mass travelling at velocities up to 13.7 m/s were performed. These are much higher than the ones required by EU and US safety devices certification standards. Finally, the material performance is evaluated under different temperatures to simulate work in diverse environmental conditions. Results attest the robustness of this natural cellular material in the range of studied conditions. Finally, numerical simulations are performed using finite element analysis in order to check the validity of the developed material model for high impact energies. Graphical abstract: